Serial assessment of inflammatory biomarkers as a prognostic factor for first-line treatment outcomes in patients with metastatic colorectal cancer: single-center retrospective study - Librenjak, Nikša; Adžić, Gordan; Kekez, Domina; Goršić, Irma; Prejac, Juraj; Pleština, Stjepko (Frontiers in Oncology, 2026)
BackgroundMetastatic colorectal cancer (mCRC) is a major cause of cancer-related mortality, with limited curative options despite advances in targeted therapies. Reliable prognostic biomarkers are needed to guide treatment. Inflammatory markers such as the neutrophil-to-lymphocyte ratio (NLR) and systemic immune-inflammation index (SII) may predict poor outcomes. This study evaluated the prognostic value of serial NLR and SII assessments in first-line mCRC therapy.MethodsIn this single-center, retrospective, observational study, we obtained data on 258 patients who started first-line systemic chemotherapy from the beginning of 2016 until the end of 2018. Baseline (pretreatment) and 3-month post-treatment values of NLR and SII were used to determine their prognostic value for treatment outcomes, which were measured as progression-free survival (PFS) and overall survival (OS).ResultsPatients were divided by pretreatment median NLR (3.19) and SII (810). Low NLR was associated with longer PFS (15.4 vs. 9.5 months, p=0.031) and OS (39.1 vs. 27.2 months, p=0.002). After 3 months, PFS difference increased (14.3 vs. 4.5 months, p<0.001); OS was longer but not significantly (35.3 vs. 20.1 months, p=0.14). Low SII after three months of therapy was linked to improved PFS (14.1 vs. 6.8 months, p<0.001) and OS (36.4 vs. 21.6 months, p=0.001), while at baseline assessment it was associated with longer OS (39.4 vs. 27.1 months, p=0.003), but not with PFS (13.9 vs. 10.6 months, p=0.11). Multivariate analysis showed pretreatment NLR and SII were independent prognostic factors for OS, but not PFS. Post-treatment NLR was prognostic for PFS only, while post-treatment SII was prognostic for both OS and PFS.ConclusionsSerial evaluation of NLR and SII could identify patients who are at increased risk of poor survival outcomes.